Transcipts: Hot vision - Samuelsson, Robin (Uppsala University, 2020)
Transcripts (in Swedish and English) of students and instructors in a chemistry course investigating deliquescence.

The dataset was originally published in DiVA and moved to SND in 2024.

Transkriberingar (på svenska och engelska) av studenter och lärare i en kemikurs som undersöker delikvescens.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Transcipts: Hot vision
Keywords: teaching experiments; undervisningsförsök; teacher training; lärarutbildning; Physics with specialization in Physics Education; Fysik med inriktning mot fysikens didaktik; Other Physics Topics; Annan fysik; Educational Sciences; Utbildningsvetenskap